Subthreshold social cognitive deficits may be a key to distinguish 22q11.2DS from schizophrenia. Issue 2 (25th March 2018) - Peyroux, Elodie; Rigard, Caroline; Saucourt, Guillaume; Poisson, Alice; Plasse, Julien; Franck, Nicolas; Demily, Caroline
Abstract : Aim: Social cognitive impairments are core features in 22q11.2 deletion syndrome (22q11.2DS) and schizophrenia (SCZ). Indeed, adults with 22q.11.2 DS often have poorer social competence as well as poorer performance on measures of social cognitive skills (emotion recognition and theory of mind, ToM) compared with typically developing people. However, studies comparing specific social cognitive components in 22q11.2DS and SCZ have not yet been widely conducted. Methods: In this study we compared performances of 22q11.2DS and SCZ on both facial emotion recognition and ToM. Patients with 22q11.2DS ( n = 18) and matched SCZ patients were recruited. After neuropsychological testing, the facial emotion recognition test assessed the patients' ability to recognize six basic, universal emotions (joy, anger, sadness, fear, disgust, and contempt). The Versailles‐situational intentional reading evaluated ToM with six scenes from movies showing characters in complex interactions (involving hints, lies, and indirect speech). Results: We show that 22q11.2DS exhibited significantly lower performance in emotion recognition than SCZ patients did, especially for disgust, contempt, and fear. This impairment seems to be a core cognitive phenotype in 22q11.2DS, regardless of the presence of SCZ symptoms. Concerning ToM, our results may highlight the same impairment level in 22q11.2DS and SCZ but require to be replicated in a larger cohort. Conclusion: Our results document the existence of threshold social cognitive deficits distinguishing 22q11.2DS from SCZ.